2016
DOI: 10.17957/ijab/15.0214
|View full text |Cite
|
Sign up to set email alerts
|

Lactifluus volemus: An Addition to the Fungi of Pakistan

Abstract: Lactifluus volemus (Fr.) Kuntze, an edible mushroom, was collected from moist temperate coniferous forests of Miandam Valley, Swat, Khyber Pakhtunkhwa. The species is reported and described for the first time from Pakistan. Distinguishing features are reddish to orange color, azonate pileus, creamy white milk, crowded gills, sub-cylindric to sub-fusiform pleuromacrocystidia, cheilocystidia and globose to subglobose reticulated spores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, L. oedematopus (described from Europe) differs from L. indovolemus by possessing smaller basidiomata (pileus 30–70 mm diam. ), fine wrinkles (smooth in L. indovolemus ) on pilear surface and longer pleurolamprocystidia (50–120 × 7–11 μm) (Van de Putte et al ). Lactifluus distantifolius (described from Thailand) has distant (4–5 l + l cm −1 ) lamellae [lamellae are crowded (14 l + l cm −1 ) in L. indovolemus ] and L. longipilus possesses long (10–130 × 3–6.5 µm) terminal pileal hairs (pileal hair is 14.7–32 × 3.1–5.6 µm in L. indovolemus ) (Van de Putte ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, L. oedematopus (described from Europe) differs from L. indovolemus by possessing smaller basidiomata (pileus 30–70 mm diam. ), fine wrinkles (smooth in L. indovolemus ) on pilear surface and longer pleurolamprocystidia (50–120 × 7–11 μm) (Van de Putte et al ). Lactifluus distantifolius (described from Thailand) has distant (4–5 l + l cm −1 ) lamellae [lamellae are crowded (14 l + l cm −1 ) in L. indovolemus ] and L. longipilus possesses long (10–130 × 3–6.5 µm) terminal pileal hairs (pileal hair is 14.7–32 × 3.1–5.6 µm in L. indovolemus ) (Van de Putte ).…”
Section: Resultsmentioning
confidence: 99%
“…Lactifluus sect. Lactifluus (Van de Putte et al , Das et al , De Crop et al ), (b) BLAST (Altschul et al 1997) searches in the public database GenBank (Clark et al ) and (c) four sequences derived from our four collections. Multiple sequence alignment was performed using MAFFT ver.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported Lactarius volemus Fr. (LVF) to be a good source of dietary fibre, protein, amino acid, fat and minerals (Khan and Sher ). The main components of LVF can be used as a primary probiotic growth factor.…”
Section: Introductionmentioning
confidence: 99%